The Unmet Needs of Women Living with Cancer in Community Setting: A Professional Concern - Ni Putu Wulan Purnama Sari (National Cancer Center - Dharmais Cancer Hospital, 2022)
Background: In the community of Surabaya, the 2nd largest city of Indonesia, women living with cancer are mostly the long-term survivors of advanced-stage cervical cancer, but the number of women living with breast cancer cannot be ignored. There were various physical and psychological problems related to the total suffering and worsening phenomena. The limited resources available in the community have led to various levels of unmet needs in their perspective. This study aimed to analyze and describe the unmet needs of female cancer survivors in the community of Surabaya. Methods: This descriptive study involved five Public Health Centers (PHCs) among 63 PHCs in Surabaya (7.94%), Indonesia, which were selected by one-stage cluster random sampling. There were 41 and 40 women living with breast and cervical cancers, respectively, participating in this study (n = 81). The Supportive Care Needs Survey – Short Form 34 (SCNS-SF34) was used to collect the data of unmet needs (r = 0.234 – 0.821; Chronbach Alpha = 0.939). Descriptive statistic was used in data analysis (frequency, Mean, and Standard Deviation). Ethical clearance was issued. Results: Most respondents were late adult married women with low socioeconomic status. They were mostly short-term survivors and already had surgery. Most of them reported a moderate level of unmet needs (Mean ± SD = 109.30 ± 27.66). Health system and information needs became their top priorities (45.75), followed by patient care and support needs (37.89), physical and daily function needs (32.20), psychological needs (31.11), and sexuality needs (22.00). There were 9.88% of respondents who reported that there were no unmet needs. Conclusions: Female cancer survivors in the community reported a moderate level of unmet needs. Health system and information needs were the most reported unmet needs